The General Elections in Indonesia as the Application of the Concept of People's Sovereignty - Arifani, Devina (Law Development Journal, 2022)
This paper aims to provide a brief explanation regarding the holding of general elections in Indonesia as a democratic party as well as a manifestation of people's sovereignty. This paper is a qualitative research using the library study method, namely by collecting reference materials from written sources, such as textbooks, dictates, newspapers, and laws. Then analyzed and reduced to get a conclusion. The conclusion of this study is the division of the types of modern democracy, currently the Republic of Indonesia is in the stage of democracy with direct supervision by the people. Supervision by the people in this case, is manifested in a democratic election administration. The drafting of laws on elections, political parties, as well as the composition and position of the new legislative body has made it easier for our society to start studying democracy.